2013
DOI: 10.1017/s0007114512006162
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial carbohydrate-degrading capacity in foal faeces: changes from birth to pre-weaning and the impact of maternal supplementation with fermented feed products

Abstract: The present study aimed at (1) describing age-related changes in faecal bacterial functional groups involved in carbohydrate degradation and in their activities in foals (n 10) from birth (day (d) 0) to 6 months (d180) and (2) investigating the effect of maternal supplementation (five mares per treatment) from d2 45 to d60 with fermented feed products on response trends over time of the foal bacterial carbohydratedegrading capacity. Maternal supplementation with fermented feed products stimulated foal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 60 publications
2
41
0
Order By: Relevance
“…It entails the growth and cellular differentiation of the rumen, which results in a major shift in the pattern of nutrients that are delivered to the intestines and liver, and then to the peripheral tissues of the animal30. Many studies have shown that the rumen development process includes anatomic development (increase in rumen mass and growth of the rumen papillae)3132, functional achievement (fermentation capacity and enzyme activity)3334, and microbial colonization (bacteria, fungi, archaea and protozoa)3536. Together, these observations suggest that anatomic, functional, and microbial development in the rumen represents an integrated system, and they should be studied together to better understand the process of rumen development.…”
Section: Discussionmentioning
confidence: 99%
“…It entails the growth and cellular differentiation of the rumen, which results in a major shift in the pattern of nutrients that are delivered to the intestines and liver, and then to the peripheral tissues of the animal30. Many studies have shown that the rumen development process includes anatomic development (increase in rumen mass and growth of the rumen papillae)3132, functional achievement (fermentation capacity and enzyme activity)3334, and microbial colonization (bacteria, fungi, archaea and protozoa)3536. Together, these observations suggest that anatomic, functional, and microbial development in the rumen represents an integrated system, and they should be studied together to better understand the process of rumen development.…”
Section: Discussionmentioning
confidence: 99%
“…For microbial analyses, one aliquot of colonic contents was held in CO 2 -saturated flasks at 38°C before inoculation. Microbial analyses were carried out as described by Julliand et al (1999) and Faubladier et al (2013). Ten-fold dilution series were prepared under O 2 -free CO 2 in an anaerobic mineral solution.…”
mentioning
confidence: 99%
“…In the present study, as the supplementation was given directly to foals, the Faubladier et al (2013) hypothesis is not applicable. Probably, the production and composition of the milk was similar and the colonization of the large intestine of the foals was performed passively through the microbiota of the respective mares (Earing et al, 2012;Faubladier et al, 2014) that did not receive any prebiotic FOS.…”
Section: Discussionmentioning
confidence: 76%
“…Faubladier et al (2013), evaluating foals of mares supplemented with prebiotics (lactic fermentation products and sprouted cereal seed), observed larger weight of these foals compared with Means followed by different letters in the columns differ according to the SNK test (P<0.05). Effects: supplementation = not significant (NS); age = 0.000; supplementation × age = NS; coefficient of variation (CV) (BL) = 2.5%; CV (TC) = 2.4%; CV (FC) = 1.1%; CV (KC) = 2.0%; CV (SC) = 1.1%.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation